Leadership Structure, Gender Diversity and Audit Quality Influence on Earnings Management in Malaysian Listed Companies - Ishak, Rokiah; Amran, Noor Afza; Manaf, Kamarul Bahrain Abdul (International Review of Management and Marketing, 2017)
The aim of this paper is to examine the effect of CEO duality, women directors and BIG 4 audit firm on real earnings manipulation (REM) proxied by cash flow from operation and discretionary expenses (DE). The sample of the study was Malaysian Public Listed Companies in year 2009-2012 with a sample of 1597 firm-year observations. Using regression analysis, this study evidences that CEO duality promote REM. Interestingly, by having BIG 4 as auditors, firms failed to prevent managers from managing the earnings figure. Further, having women as directors in companies also do not help firms to mitigate the earnings manipulation problem. This paper contributes to the literature on earnings management by presenting evidence on the management of cash flows items and DE, which has received little attention to date. Keywords: CEO Duality, Women Directors, BIG 4 Auditor, Real Earnings Management JEL Classifications: M40, M42, M49